Development of guidelines to improve the sustainability of the territorial economy through diversification territorial production complex with a dominant industry - I. S. Borisova (Путеводитель предпринимателя)
The paper proposes an approach to improve the sustainability of the territorial-production complex (TPC) with dominant industry on the basis ofthe diversification of the economy, represented by the mechanism of the WPK, based on the determination of the extent of diversification of major changes informs of support and selection criteria of comparison for subsequent decisions.